Identify Resources Activated by Students When Solving Straight Motion Kinematics Problems with Different Representation - Nur Utami Amaliah; Sutopo Sutopo; Eny Latifah; Hutkemri Zulnaidi (Jurnal Pendidikan Sains, 2024)
This research aims to explore kinematic resources in linear kinematics by utilizing different forms of problem representation. The study was conducted by administering 15 reasoned multiple-choice questions to 146 high school students from three districts in Central Sulawesi, Indonesia. The research instrument covers topics in linear kinematics, including distance, displacement, speed, and velocity, presented through diagrammatic representations, graphs, and mathematical equations. The students’ written answers were analyzed both quantitatively and qualitatively. Quantitative analysis was conducted to determine descriptive statistics from the data, while qualitative analysis identified the resources students activated when solving these questions. The findings reveal that the various resources students activate include Phenomenological Primitives (P-Prims), Conceptual Resources, and Procedural Resources. Procedural Resources are more frequently activated when students solve problems presented as mathematical equations. In contrast, in response to visual representations such as diagrams and graphs, students tend to activate “What You See Is What You Get” (WYSIWYG) as P-Prims.DOI: 10.17977/jps.v12i22024p076